Youth and the Structural Denial of the Right to Human Dignity: An Interdisciplinary Theoretical and Epistemological Approach - Santhosh-Kumar Appu (Religions)
There are discriminatory, structured, opaque human rights violations that keep the socioeconomically vulnerable subservient, a social problem that goes against the core Christian principle: humans are created in the image of God and all share equal dignity. Studies show that sociocultural, political, and economic elements are available in society, which form into clusters, namely social representations, helping people to categorize others and interact with her/him. They carry with them the historical consciousness, providing the people with social-living tools such as social identity and the like. The qualitative empirical research conducted among the Catholic youth of Tamil Nadu, India, showed that the enslaving semantic elements contained in the social knowledge facilitate the youth to affiliate with a group and to disaffiliate from another. Caste-ridden endogamic semantic elements are part of this knowledge. This affects individual as well as social cognition. Therefore, besides conceptual understanding, epistemological approaches are necessary to eliminate the enslaving elements contained in social knowledge. This is possible through the Ego–Alter dialogue. Ego stands for an individual, group, institution, movement, or anything similar. Alter can stand for social knowledge, which is available in society.